Investigation of fuel temperature and injection timing effects on ammonia direct injection in an optical engine - Valentin Scharl; Karl Oskar Pires Bjørgen; David Robert Emberson; Terese Løvås (Applications in Energy and Combustion Science)
This work investigates the effects of fuel temperature and injection timing on ammonia direct injection in an optical engine using a multi-hole injector. Flash-boiling may occur over various engine-relevant conditions due to ammonia’s high vapor pressure. This phenomenon impacts spray characteristics and, in severe cases, facilitates cavitation inside the nozzle. Both fuel temperature and injection timing (i.e., ambient conditions during injection) impact the intensity of flash-boiling during fuel injection. Therefore, this work varies fuel temperature (from 320K to 388K) and injection timing (from −60CADaTDC (crank angle degrees after top dead center) to −6CADaTDC) to assess their impact on injection mass flux, discharge coefficients, and macroscopic spray characteristics using an ammonia injection pressure of 200bar. For this purpose, the injection mass is measured by analyzing exhaust gas compositions during engine operation with ammonia injections but without combustion. In addition, diffuse background illumination (DBI) images capture the liquid phase of the fuel spray to characterize spray behavior. The findings reveal that increasing fuel temperature decreases ammonia’s injection mass by up to 12.8% but has little impact on discharge coefficients for late injection timings and high in-cylinder pressures. However, discharge coefficients decrease by up to 17.4% (from 0.58 to 0.48) for early injection timings if fuel temperatures are high. The individual sprays of the 6-hole GDI injector may collapse into a uniform spray at high-density conditions without flash-boiling or under strongly flash-boiling conditions. The findings clarify the impact of ammonia’s high vapor pressure on injection mass and prove the relevance of different spray collapse mechanisms in ammonia direct injection engines.